How relational and strategic leadership shape organizational culture - Lebusa, Libuseng Mampolokeng (Rhodes University, Faculty of Commerce, Rhodes Business School, 2020)
The study aims at analysing how relational and strategic leadership shapes the culture of an organization, using as a case study the SOS Children's Village Lesotho in Quthing District. As an International Federation, SOS Children's Village espouses four values, namely Courage, Trust, Commitment, and Accountability. The case was selected because SOS Children's Village's performance in Lesotho has been outstanding, due to employee commitment in the organization. The review of the literature drew upon three theories: the theory of organizational culture by Schein (2010), which shed a light on cultural embedding mechanisms, the relational leadership components of Komives, S, Lucas, N, and McMahon, T (1998), and the strategic leadership roles of Ireland and Hitt (1999). This study adopted a deductive qualitative research method, where structured interviews supplemented with documents were used to collect data. Thematic analysis and pattern matching analysed the data with the aid of a pre-developed codebook that identify theoretical codes and themes in the data. The findings confirmed that with the use of cultural embedding mechanisms, relational and strategic leadership shaped the culture of commitment. The main characteristics of the culture of the commitment of SOS Quthing are punctuality, teamwork, and individual initiative. Relational and strategic leadership behaviours helped to create a culture of commitment through the fair and equitable allocation of resources, the inclusion of employees in decision making, having an orientation program for new employees, giving rewards and recognition, holding regular meetings, supervision, utilizing the online collaboration system and the systematic development of human capital. The literature supported the study results. The study acknowledges the limitations and delimitations of the research. The study's contribution was in identifying how leadership behaviours operate through cultural embedding mechanisms to "identify" creates a culture of commitment. In conclusion, managerial recommendations were made for SOS to strengthen their leadership behaviours further and further research recommendations.
Keywords: SOS Quthing Children's Village -- Management; Corporate culture; Corporate culture -- Lesotho -- Quthing; Leadership -- Lesotho -- Quthing; Nonprofit organizations -- Lesotho -- Quthing